Inhibition by zinc of rhinovirus protein cleavage: interaction of zinc with capsid polypeptides. - Korant, B D (1976)
Zinic ions rapidly inhibit virus production in HeLa cells infected with human rhinovirus type 1A and lead to the accumulation of human rhinovirus type 1A precursor polypeptides. The degree to which cleavage of these precursors is inhibited is directly dependent on the quantity of cell-associated zinc. Proteolysis resumes after the removal of zinc-containing medium, and the accumulated viral precursors are cleaved predominantly to stable virus polypeptides. The precursors stabilized at the lowest zinc levels are those that contain capsid protein sequences. Furthermore, added zinc is bound to human rhinovirus type 1A capsids and prevents them from forming crystals. Zinc-resistant mutants display antigenic alterations in coat proteins. These results suggest that zinc complexes with rhinovirus coat proteins and alters them so that they cannot function as substrates for proteases or as reactants in the assembly of the virus particles.